Supply Chain Logistics in Agricultural Sector – Assessing Opportunities for Competitiveness Increase - Tlektes Espolov; Aidos Espolov; Kanat Tireuov; Zharylkap Zharylkassyn; Margulan Keneyev; Zhenisbek Suleimenov (International Journal of Supply Chain Management, 2020)
Abstract—This article discussed the problem of logistics management of the agricultural supply chain on the example of Kazakhstan. The article aims to justify the impact of logistics as a factor of increasing the supply chain competitiveness in the agricultural sector using Kazakhstan as a case study. The relevance of the topic is conditioned by the fact that agriculture is one of the budget-forming sectors in Kazakhstan. Thus, the improvement of supply chains in this area is a factor for increasing the competitiveness of the national economy. The transportation industry is determined to be the key factor that affects supply chains. For the Republic of Kazakhstan, the investment in large road projects is directly proportional to the production cost in the agricultural sector with a time lag of several years. Such national projects with the international partners’ participation promoted the regional development of the country and thereby made the pattern of national development less uneven. Once the projects completed, the domestic demand for various goods and the profitability of the agricultural sector have increased. Taking into account the country context was offered a conceptual approach to the development of the logistic infrastructure, as a level regional system in Kazakhstan. At the level of unique logistics groups and the national coordinating council an integrated logistics management system was developed.